2022
DOI: 10.3390/toxics10070341
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Environmentally Persistent Free Radicals in PM2.5 and the Influence of Air Pollutants in Shihezi, Northwestern China

Abstract: Environmentally persistent free radicals (EPFRs) are a kind of hazardous substance that exist stably in the atmosphere for a long time. EPFRs combined with fine particulate matter (PM2.5) can enter the human respiratory tract through respiration, causing oxidative stress and DNA damage, and they are also closely related to lung cancer. In this study, the inhalation risk for EPFRs in PM2.5 and factors influencing this risk were assessed using the equivalent number of cigarette tar EPFRs. The daily inhalation ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Therefore, Fairbanks primarily has nonextreme air quality, but may be a concern for public health after prolonged temperature inversion in which we observe higher concentration of EPFRs (see Section 3.2). As shown in Table 1, this value in Fairbanks is comparable to that in Irvine, CA, 62 but lower than those in highly polluted Chinese cities including Shihezi, 12 Xi'an, 11 and Beijing. 5 EPFRs with a semiquinone type structure are known to be redox active, which means that they can induce the formation of ROS upon inhalation and respiratory deposition to lung lining fluid, causing oxidative stress and adverse health effects.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Therefore, Fairbanks primarily has nonextreme air quality, but may be a concern for public health after prolonged temperature inversion in which we observe higher concentration of EPFRs (see Section 3.2). As shown in Table 1, this value in Fairbanks is comparable to that in Irvine, CA, 62 but lower than those in highly polluted Chinese cities including Shihezi, 12 Xi'an, 11 and Beijing. 5 EPFRs with a semiquinone type structure are known to be redox active, which means that they can induce the formation of ROS upon inhalation and respiratory deposition to lung lining fluid, causing oxidative stress and adverse health effects.…”
Section: Discussionmentioning
confidence: 73%
“…62 In contrast, a study in Xi'an 11 observed a positive correlation of EPFR v with ozone in the summer, and an annual a positive correlation between EPFR m and O 3 was observed in Shihezi. 12 A weak correlation between EPFR m and O 3 is observed (Figure S6e), which indicates that EPFRs are not efficiently quenched by heterogeneous reactions with O 3 .…”
Section: Correlation Of Gaseous Pollutants With Epfrsmentioning
confidence: 96%
See 1 more Smart Citation
“…The g-values of solid fuel-burning EPFRs decrease (from ∼2.0037 to ∼2.0030) when exposed to air (Table S3), and exhibit greater variation than those of atmospheric EPFRs. The shift in g-values suggests that carbon-centered radicals with adjacent oxygen atoms exhibit greater reactivity than carbon-centered radicals . However, the line widths either remain unchanged or increase slightly (Table S4), suggesting the formation of more complex structures, such as delocalized electrons and multiple radicals .…”
Section: Resultsmentioning
confidence: 99%
“…Branch vibratory picking requires picking each branch individually, which can be time-consuming and inefficient, requiring a significant amount of human resources [18][19][20][21][22]. On the other hand, canopy vibratory picking involves directly vibrating the crown of the tree, increasing the chances of contact between the shaking rod and the fruit [23][24][25][26][27][28][29][30]. However, this method also poses a higher risk of fruit damage and potential harm to the fruit tree itself.…”
Section: Introductionmentioning
confidence: 99%